Assessment of consumer awareness and empowerment levels in Surat city and surrounding rural areas: a review of indexes developed - Prasad, B. Devi and Trivedi, Vimal (Nagarlok)
The data for the present paper is part of a major study sponsored by the Indian Institute of Public Administration, New Delhi and conducted in Surat city and its adjacent rural area to understand the grievance redressal practices in the health and health insurance services in the region. As part of this study, two indexes were developed to assess the consumer awareness & knowledge, and consumer empowerment levels. The data gathered from the sample respondents using the two indexes are presented here. Thus, the aim of this paper is to examine the trends in the consumers$1 (Bawareness about their rights and information about actions considered to be effective in protecting their rights in the changing socio economic scenario. A multistage representative sample of 847 households from Surat city and five villages in its surrounding area was consulted to explore the differences in the trends. Using the data generated from the sample respondents, an attempt was made in this paper to ascertain the relationship between consumer awareness & knowledge, and consumer empowerment levels and the demographic variables such as rural-urban residence, sex, age, income and educational levels. The findings broadly cover three aspects i.e i) consumer awareness & knowledge mediated by certain demographic variables, ii) identification of actions effective in promoting and protecting rights of consumers, and iii) variables which influence the perceptions of respondents in considering them as effective. Based on the study findings suggestions were offered for the improvement of consumer education and empowerment interventions. - Reproduceds
Keywords: Consumer awareness, Consumers protection